Changes and Continuities in Local Articulations of Life, Illness and Healing in Rural Africa: A Case Study of the Iraqw of North-Central Tanzania - Lawi, Yusufu (Tanzania Journal for Population studies and Development, 2008)
This article explores the ways in which rural communities in Tanzania perceived and articulated human life, illness, and death in the distant past, and the manner and extent to which such perceptions have changed in recent times. It uses a case study of the Iraqw ethnic community in the Mbulu-Hanang’ area to discern the manner in which rural people in the late pre-colonial and early colonial periods understood and elaborated on life in general, illness types and causality, and how healing comes about. Towards the end a brief analysis is made of the manner in which these traditional perceptions have been changing in recent years. The article concludes that the late 19th century Iraqw perceptions of life, illness, and death were based on a mix of rational and mystic ideas, which were themselves closely bound with concrete social relations obtaining in the community, and that the recent partial transformations in such perceptions are motivated by continuing changes in the local cultural context. A brief statement on the practical significance of these conclusions closes the discussion.